Little Santa - Agee, Jon, (Dial Books for Young Readers, an imprint of Penguin Group (USA) Inc., 2013)
A resident of the North Pole with the ability to slide up and down chimneys meets a flying reindeer and some industrious elves, in this fictional biography of Santa Claus.